Math, asked by aryankumar6557, 1 year ago

Can you please solve this question. If any user answered it correctly than I will make it brainlist​

Attachments:

Answers

Answered by anupampr79
1

Here is the answer...

Hope it helps!!!

Plz mark as brainliest...

Attachments:
Answered by Anonymous
2

\bold\red{\underline{\underline{Answer:}}}

\bold{=>2(a^{2}-\frac{1}{a^{2}})}

\bold\blue{Explanation}

\bold{a^{2}+b^{2}=(a+b)^{2}-2ab}

\bold\orange{Given:}

\bold{(a-\frac{1}{a})^{2}+(a+\frac{1}{a^{2}})}

\bold\green{\underline{\underline{Solution}}}

\bold{By \ identity \ a^{2}+b^{2}=(a+b)^{2}-2ab}

\bold{=>(a-\frac{1}{a}+a+\frac{1}{a})^{2}-2[(a-\frac{1}{a})(a+\frac{1}{a})]}

\bold{=>(2a)^{2}-2(a^{2}-\frac{1}{a}^{2})}

\bold{=>4a^{2}-2a^{2}-\frac{2}{a^{2}}}

\bold{=>2a^{2}-\frac{2}{a^{2}}}

\bold{=>2(a^{2}-\frac{1}{a^{2}})}

Similar questions